Adoptive children and families: In search of their origins - Cordella, Barbara; Rossini, Susanna; Elia, Paola (Quaderni di Psicologia Clinica, 2022)
The study presented aimed to explore the way in which a group of adoptive mothers (37) relate to the “search for biological origins” event by their adoptive children. Interviews were collected, studied through a cluster analysis and a subsequent analysis of multiple correspondences. The study highlights the distance between the experiences of the mothers interviewed and the role foreseen for them by the law (149/2001). The need to show oneself available to accompany the children in their exploration contrasts with the experience of identity loss that this exploration evokes. On the other hand, the difficulty of adoptive mothers in recognizing the specificity of their own family configuration, which does not conform to a supposed model of normality, emerges.
Keywords: Adoptive parents; search for origins; text analysis